The leucine-rich region of Flightless I interacts with R-ras to regulate cell extension formation - Arora, P. D. (Mol Biol Cell, 2018)
Flightless I (FliI) is a calcium-dependent, actin severing and capping protein that localizes to cell matrix adhesions, contributes to the generation of cell extensions, and colocalizes with Ras. Currently, the mechanism by which FliI interacts with Ras to enable assembly of actin-based cell protrusions is not defined. R-Ras, but not K-ras, H-ras, or N-ras, associated with the leucine-rich region (LRR) of FliI. Mutations of the proline-rich region of R-ras (P202A, P203A) prevented this association. Knockdown of Ras GTPase-activating SH3 domain-binding protein (G3BP1) or Rasgap(120) by small interfering RNA inhibited the formation of cell extensions and prevented interaction of R-ras and G3BP1 in FliI wild-type (WT) cells. Pull-down assays using G3BP1 fusion proteins showed a strong association of R-ras with the C-terminus of G3BP1 (amino acids 236–466), which also required the LRR of FliI. In cells that expressed the truncated N-terminus or C-terminus of G3BP1, the formation of cell extensions was blocked. Endogenous Rasgap(120) interacted with the N-terminus of G3BP1 (amino acids 1–230). We conclude that in cells plated on collagen FliI-LRR interacts with R-ras to promote cell extension formation and that FliI is required for the interaction of Rasgap(120) with G3BP1 to regulate R-ras activity and growth of cell extensions.